2014
DOI: 10.1002/ehf2.12014
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function in patients supported with left ventricular assist device and with heart transplant

Abstract: Sexual dysfunction occurs in patients with LVAD support and may be more prominent than after HTx. Problems limiting sexual function related to physiological, psychological, and equipment merit consideration during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…51 In patients with advanced left heart failure who have left ventricular assist devices (LVADs), device-related issues frequently contribute to sexual dysfunction and SHRQoL, akin to our observations, and in one study the impact of LVADs on sexual health tracked with the development of depression, known to be common in PAH. [27][28][29] While we did not quantify anxiety and depression in this study, mental health is frequently impacted in individuals with chronic diseases characterized by equipment and physical challenges, 52,53 which suggests that these issues may need to be addressed concurrently in PAH. Given the fact that PAH treatments are challenging but reduce symptoms and prolong survival, it is plausible that treatment with parenteral therapy may negatively impact sexual health and patients' engagement in sexual behaviors, but not affect (or at least beneficially offset) other aspects of HRQoL.…”
Section: Scalementioning
confidence: 96%
See 1 more Smart Citation
“…51 In patients with advanced left heart failure who have left ventricular assist devices (LVADs), device-related issues frequently contribute to sexual dysfunction and SHRQoL, akin to our observations, and in one study the impact of LVADs on sexual health tracked with the development of depression, known to be common in PAH. [27][28][29] While we did not quantify anxiety and depression in this study, mental health is frequently impacted in individuals with chronic diseases characterized by equipment and physical challenges, 52,53 which suggests that these issues may need to be addressed concurrently in PAH. Given the fact that PAH treatments are challenging but reduce symptoms and prolong survival, it is plausible that treatment with parenteral therapy may negatively impact sexual health and patients' engagement in sexual behaviors, but not affect (or at least beneficially offset) other aspects of HRQoL.…”
Section: Scalementioning
confidence: 96%
“… 24 26 Finally, anxiety and depression is common in PAH and it is conceivable that this may be driven in part by as yet unquantified effects on sexual relationships and feelings of intimacy. 27 29 …”
Section: Introductionmentioning
confidence: 99%
“…8 Sexual problems can be related to other HF treatment such as device therapy or heart transplantation. 24,25 In a small study of 31 patients, 29% left ventricular assist device (LVAD) patients and 71% heart transplant patients reported being content with sexual activity; however, satisfaction with sex life was lower in transplant patients compared with HTx patients (7.6 ± 3.1 for HTx on a visual analogue scale vs. 3.9 ± 4.0 for LVAD patients, P = 0.017). 24 In addition to HF symptoms, comorbidity, and HF treatment, several other factors such as psychological factors (depression, anxiety) can contribute to sexual problems.…”
Section: Prevalence Of Sexual Problems In Heart Failure Patientsmentioning
confidence: 99%
“…24,25 In a small study of 31 patients, 29% left ventricular assist device (LVAD) patients and 71% heart transplant patients reported being content with sexual activity; however, satisfaction with sex life was lower in transplant patients compared with HTx patients (7.6 ± 3.1 for HTx on a visual analogue scale vs. 3.9 ± 4.0 for LVAD patients, P = 0.017). 24 In addition to HF symptoms, comorbidity, and HF treatment, several other factors such as psychological factors (depression, anxiety) can contribute to sexual problems. 5 More general factors that are related to sexual function might be relevant to consider in the HF population as well, such as age, lifestyle, or problems in a relationship.…”
Section: Prevalence Of Sexual Problems In Heart Failure Patientsmentioning
confidence: 99%
“…These authors concluded that sexual dysfunction is prevalent in patients with LV assist device support and that it may be more prominent in these patients than after cardiac transplantation. In addition, they state that ‘problems limiting sexual function related to physiological, psychological, and equipment merit consideration during follow‐up’ . Lastly, Steinbeck et al have studied a first potential biomarker of skeletal muscle wasting, the C ‐terminal agrin fragment, in patients with HF …”
Section: Co‐morbidities and Heart Failurementioning
confidence: 99%